CELLULASE ACTIVITY OF RIZOSFER BACTERIA OF KETAPANG PLANTS (Terminalia catappa L.) - Rosmania, Rosmania; Widjajanti, Hary; Nurnawati, Elisa (BIOVALENTIA: Biological Research Journal, 2023)
Cellulose, a natural biopolymer produced by plants, undergoes enzymatic breakdown by cellulase, cleaving the monomer's β-1,4 glycosidic bonds. Cellulolytic bacteria, producers of cellulase, can be isolated from plant rhizospheres, like Ketapang (Terminalia catappa L.), abundantly found in the Biology Department at Universitas Sriwijaya, South Sumatra, Indonesia. This study aimed to isolate cellulolytic bacteria from Ketapang rhizosphere soil and assess their cellulase activity. The spread plate method on selective Carboxy Methyl Cellulose Agar (CMC agar) was used for bacterial isolation, and cellulase activity was measured using the DNS method (3.5-dinitro salicylic acid). Results yielded 22 isolates of cellulolytic bacteria capable of growth on selective CMC agar. Thirteen isolates, identified through a screening test, produced cellulase, forming clear zones post-addition of 0.1% Congo Red and 1 M NaCl. Cellulolytic activity indices for these isolates ranged from 0.02 to 2.6 mm. The highest indices (IAS) and cellulase activities were observed in BS10, BS4, and BS22, with IAS values of 2.64, 2.12, and 1.71, and cellulase activities of 354.99 U/ml, 9.42 U/ml, and 9 U/ml, respectively. Identification results suggested that isolate BS10 bore similarities to the genus Zoogloea, while isolates BS4 and BS22 showed similarities to the genus Bacillus.